The Utility of the MCMI-III in Parental Competency Assessments. Issue 3 (27th May 2019) - Bueno Castellano, Christina V.; Brandwein, David R.; Conti, Richard P.; Gubi, Aaron A.; Marks, Donald R.; Bilach, Thomas J.
ABSTRACT: Child welfare agencies and legal authorities have frequently turned to psychologists to conduct parental competency assessments (PCA) to inform decisions aimed to advocate the best interests of children and protect them from maltreatment. The Millon Clinical Multiaxial Inventory–Third Edition (MCMI-III) is an empirically supported measure that is commonly used in the context of these examinations. This study compared the MCMI-III performance of an American-based PCA sample with previously published studies in the civil parenting literature and further explored differences across gender groups. Results revealed subclinical elevations in the "normal quartet" that were generally consistent with child custody litigants (CCE) and non-American PCA examinees in previous studies. The PCA sample produced higher rates of psychiatric pathology as compared to the CCE sample and the clinical population more generally. American and non-American PCA examinees endorsed similar rates of pathology, though American PCA examinees produced significantly higher scores on Antisocial and Drug Dependence scales. Results are suggestive of demographic differences that may account for inconsistent findings across studies.